Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 1 - Review: 124



Work Step by Step

Using order of operations, the expression $ \dfrac{(3-5)^2+(-1)^3}{1+2(3-(-1))^2} $ simplifies to \begin{array}{l} \dfrac{(-2)^2-1}{1+2(3+1)^2} \\\\= \dfrac{4-1}{1+2(4)^2} \\\\= \dfrac{3}{1+2(16)} \\\\= \dfrac{3}{1+32} \\\\= \dfrac{3}{33} \\\\= \dfrac{1}{11} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.